Ice content and interannual water storage changes of an active rock glacier in the dry Andes of Argentina - Halla, Christian; Blöthe, Jan Henrick; Tapia Baldis, Carla Cintia; Trombotto, Dario Tomas; Hilbich, Christin; Hauck, Christian; Schrott, Lothar
The quantification of volumetric ice and water contents in active rock glaciers is necessary to estimate their role as water stores and contributors to runoff in dry mountain catchments. In the semi-arid to arid Andes of Argentina, active rock glaciers potentially constitute important water reservoirs due to their widespread distribution. Here however, water storage capacities and their interannual changes have so far escaped quantification in detailed field studies. Volumetric ice and water contents were quantified using a petrophysical four-phase model (4PM) based on complementary electrical resistivities (ERT) and seismic refraction tomographies (SRT) in different positions of Dos Lenguas rock glacier in the Upper Agua Negra basin, Argentina. We derived vertical and horizontal surface changes of the Dos Lenguas rock glacier, for the periods 2016?17 and 2017?18 using drone-derived digital elevation models (DEM). Interannual water storage changes of −36 mm yr−1 and +27 mm yr−1 derived from DEMs of Difference (DoD) for the periods 2016?17 and 2017?18, respectively, indicate that significant amounts of annual precipitation rates can be stored in and released from the active rock glacier. Heterogeneous ice and water contents show ice-rich permafrost and supra-, intra- and sub-permafrost aquifers in the subsurface. Active layer and ice-rich permafrost control traps and pathways of shallow ground water, and thus regulate interannual storage changes and water releases from the active rock glacier in the dry mountain catchment. The ice content of 1.7?2.0 × 109 kg in the active Dos Lenguas rock glacier represents an important long-term ice reservoir, just like other ground ice deposits in the vicinity, if compared to surface ice that covers less than 3 % of the high mountain catchment. Fil: Halla, Christian. Universitat Bonn; Alemania Fil: Blöthe, Jan Henrick. Universitat Bonn; Alemania Fil: Tapia Baldis, Carla Cintia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...